2019
DOI: 10.1016/j.ahj.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Reliable in vivo intravascular imaging plaque characterization: A challenge unmet

Abstract: Intravascular imaging has enabled in vivo assessment of coronary artery pathology and detection of plaque characteristics that are associated with increased vulnerability. Prospective invasive imaging studies of coronary atherosclerosis have demonstrated that invasive imaging modalities can detect lesions that are likely to progress and cause cardiovascular events and provided unique insights about atherosclerotic evolution. However, despite the undoubted value of the existing imaging techniques in clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…In this context, intravascular imaging techniques detecting the plaque composition (e.g. virtual-histology intravascular ultrasound or the combination of optical coherence tomography with near-infrared spectroscopy [48]) would allow additional lesion-specific features to be determined, besides improving the 3D vessel reconstruction. In the present study, only the short-term (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, intravascular imaging techniques detecting the plaque composition (e.g. virtual-histology intravascular ultrasound or the combination of optical coherence tomography with near-infrared spectroscopy [48]) would allow additional lesion-specific features to be determined, besides improving the 3D vessel reconstruction. In the present study, only the short-term (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although based on the analysis of only three SFA lesions, this further confirms that the complex interplay of different, heterogeneous events probably determines the intervention outcome after 6 months follow-up. Intravascular imaging modalities allow detecting the arterial wall composition [27] and might be crucial to gain insights into the ISR process. Besides providing information on the baseline lesion tissue composition and plaque features potentially determining local heterogeneous responses to the intervention, details on the post-intervention arterial tissue changes would suggest whether phenomena of neoatherosclerosis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular imaging modalities allow detecting the arterial wall composition [27] and might be crucial to gain insights into the ISR process. Besides providing information on the baseline lesion tissue composition and plaque features potentially determining local heterogeneous responses to the intervention, details on the post-intervention arterial tissue changes would suggest whether phenomena of neoatherosclerosis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular ultrasound (IVUS) and optical coherence tomography (OCT) were the first invasive imaging techniques that were used to study plaque pathobiology and provided unique insights about the mechanisms that regulate plaque evolution. Validation studies using histology as the gold standard have demonstrated the advantages but also the limitations of IVUS and OCT in assessing plaque characteristics and led research toward the development of novel invasive imaging modalities that were able to overcome the drawbacks of the first techniques (8)(9)(10)(11). Near infrared spectroscopy (NIRS), photoacoustic imaging (IVPA), near infrared fluorescence imaging (NIRF), and time resolved fluorescence spectroscopy (TRFS) imaging are some of these invasive imaging techniques that were introduced to provide additional information about vessel pathology and biology.…”
Section: Introductionmentioning
confidence: 99%